Perancangan Interior Pusat Informasi Ikan Hias Air Tawar di Surabaya - Khuntardi, Daniel (Intra, 2014)
In fact, Ornamental Fish breeding is inspiring people who loves ornamental fish. Not only because the beauty of the fish but also people can make some money from their fishes which ready to be sold in the fish market. Interior Design of Ornamental Fish Information Centre is the place for people to get some information about ornamental fish and to be the place for ornamental fish lover and breeder to share their experience and knowledge. The facilities are lobby, cafÃ©, show room, fish care area, mating fish area, fish sales area, accessories, locker, and toilet. The concept design is sterilised fresh water collected from sterilisation process then implemented to the design to create a good atmosphere and comfortable place.